Transcatheter Aortic Valve Replacement for Degenerated Transcatheter Aortic Valves: The TRANSIT International Project. (7th June 2021) - Testa, Luca; Agnifili, Mauro; Van Mieghem, Nicolas M.; Tchétché, Didier; Asgar, Anita W.; De Backer, Ole; Latib, Azeem; Reimers, Bernhard; Stefanini, Giulio; Trani, Carlo; Colombo, Antonio; Giannini, Francesco; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Transcatheter aortic valve replacement (TAVR) has determined a paradigm shift in the treatment of patients with severe aortic stenosis. However, the durability of bioprostheses is still a matter of concern, and little is known about the management of degenerated TAV. We sought to evaluate the outcomes of patients with a degenerated TAV treated by means of a second TAVR. Methods: The TRANSIT is an international registry that included cases of degenerated TAVR from 28 centers. Among around 40 000 patients treated with TAVR in the participating centers, 172 underwent a second TAVR: 57 (33%) for a mainly stenotic degenerated TAV, 97 (56%) for a mainly regurgitant TAV, and 18 (11%) for a combined degeneration. Overall, the rate of New York Heart Association class III/IV at presentation was 73.5%. Results: Valve Academic Research Consortium 2 device success rate was 79%, as a consequence of residual gradient (14%) or regurgitation (7%). At 1 month, the overall mortality rate was 2.9%, while rates of new hospitalization and New York Heart Association class III/IV were 3.6% and 7%, respectively, without significant difference across the groups. At 1 year, the overall mortality rate was 10%, while rates of new hospitalization and New York Heart Association class III/IV were 7.6% and 5.8%, respectively, without significant difference across the groups. No cases of valve thrombosis were recorded. Conclusions: Selected patients with a degenerated TAV may be safely and successfully treated by means of a second TAVR. This finding is of crucial importance for the adoption of the TAVR technology in a lower risk and younger population. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04500964.